Quantitive Study on Some Aspect of Occipital Area in Domestic Cat (Felis catus) - Uddin, M; Hossain, ME; Islam, MS; Hossain, MB; Islam, KN (International Journal of Natural Sciences, 2016)
This study was planned to investigate some aspects of the morphometric characteristics of the occipital bone and foramen megnum in domestic cat (Felis catus). Twenty adult domestic cat including 10 males and 10 female cats were euthanized using diazepam (@ 20 mg/kg) and their skulls were macerated to give morphometric parameters. Student t-test with level of significance set at 5% (p < 0.05) was used to analyze the obtained values. The height of occipital triangle, width of occipital condyles, width of jugular process were significantly larger in male than female. The mean height and width of the foramen magnum were 1.32 ± 0.09 cm and 1.35 ± 0.08 cm, respectively, while the foramen index was below 100 at 90.72 ± 4.93. Parameters for the foramen magnum index showed significant difference between both sexes at p < 0.05. The foramen magnum showed shape variations and there were multiple hypoglossal foramina in over 80% of the cats. The morphometric values of the occipital bone and foramen magnum and clinical anatomy of the occipital region of the domestic cats provide an important baseline for further research in this field and could help in the better diagnosis, classification, and treatment of diseases related to this region and serve as a future reference defining an anatomic range. International Journal of Natural Sciences (2013), 3(1-4) 18-21